Pediatric nursing : Thomson Delmar Learning's Nursing Review Series - Stein, Alice (Clifton Park, NY : Thomson Delmar Learning, 2007)
Each text in teh series is designed around teh most current test plan for the NCLEX-RN and provides a focused and complete content review in each subject area.
Growth and development -- Multisystem stressors -- Neurosensory system -- The cardiovascular sysem -- The hematologic sysytem -- The respiratory system -- The gastrointestinal system -- The genitourinary system -- The musculoskeletal system -- The endocrine system -- The integumentary system -- Pediatric oncology
Keywords: ADOLESCENT DEVELOPMENT; CHILD DEVELOPMENT